OPTIMASI STRUKTUR JACKET LEPAS PANTAI DENGAN ANALISIS PERMODELAN KOMPUTASI 3D NONLINIER PUSHOVER - Amin Sundoro; Syahril Taufik (SAINSTECH: JURNAL PENELITIAN DAN PENGKAJIAN SAINS DAN TEKNOLOGI, 2021)
ABSTRACT This study emphasizes the collapse of the offshore jacket platform structure model due to lateral loads, namely environmental loads with the help of USFOS computing software. The optimized platform structure model is the A model with 4 legs with a combination of X, V, Chevron, and K diagonal bracings. Then, step by step the bracing is progressively reduced until the first yield load level of the component is below 1 or the structure does not meet the design level criteria. The analysis used is nonlinear pushover from extreme storms. The platform model A was analyzed from 8 metocean directions and the next model was analyzed using the storm direction with the smallest RSR value from model A, namely the direction of 225°. The results of the analysis show changes in the global collapse mechanism, components that experience the first yield and changes in ductility. From the results of the scoring between the weight ratio of model A to the weight of the models with the redundancy value, the largest value obtained is the Platform E hybrid model with 4X bracing, 2 Chevrons, and 4 vertical diagonal models K with steel grade S315. The weight that can be optimized by the E Hybrid model from the A model is 101,801 kN, optimum 2,88% and redudancy factor reached 198.20%. Keywords: Extreme storm, Collapse mechanism, Nonlinear Pushover, Redundancy, Ductility